PERANCANGAN PROTOTYPE WEB APP SISTEM LAYANAN PEMESANAN DAN INFORMAS CAR WASH DI SOLO - Zamzami, Abdullah Ibrahim; Rahman, Yanuar; Dwija Putra, I Dewa Alit (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2024)
The populationoftwo-wheeledand four-wheeled vehicles in Indonesia willreach more than 141 million units in 2021, encouraging the growth of the car wash industry. The challenge of customer queues in small areas was highlighted, sparking the idea of a technology-based solution. Through a design thinking approach,awebappfororderingcarwashinformationwasdesignedtoovercome the problem of limited land area and insufficient human resources. Using Figma indesigning userinterfaces (UI) prioritizes harmonious layout elements,contrast, and clear typography.Prototype testing is carried out to ensure the solution meets user needs. The literature review includes Design Thinking, User Interface (UI), User Experience (UX), User Flow, Figma, and Usability Testing. It is hoped that implementing this WebApp can increase car wash operational efficiency,reduce customer queues, and provide a better customer experience.